Use of wood dust fly ash from an industrial pulverized fuel facility for rendering. (20th November 2018) - Fuller, Aaron; Stegmaier, Michael; Schulz, Norbert; Menke, Martin; Schellhorn, Hans; Knödler, Friedrich; Maier, Jörg; Scheffknecht, Günter
Highlights: Wood fly ash is a viable component for render mortars. Wood dust fly ash from reducing conditions has excellent resistance to weathering. Wood fly ash from reducing conditions can replace a significant amount of cement. Wood fly ash from reducing conditions is good in mixtures for atmospheric CO2 sinks. Abstract: Wood dust II fly ash, which was generated after boiler retrofit (implementation of low-NOx burners combined with over-fire air), apparently is an enhanced quality for rendering. This is attributed to the mineral phases formed, an increase in the amount of free lime, and performance test results. After accelerated aging tests, the wood dust II fly ash showed no visible occurrence of cracks or detachment of the render base coat from the substrate. Tensile strength values met the applicable limit requirement of 8 MPa. The results contribute to a sustainable ash management for wood fly ash from pulverized fuel facilities.